The effect of classroom management using the visual auditory kinesthetic learning model on mathematics learning outcomes on the material of a system of linear equations of two variables - Kemri, Tiara Widia; Hasibuan, Lily Rohanita; Siregar, Sakinah Ubudiyah (Universitas Islam Negeri Raden Intan Lampung, 2024)
This study aims to find out the effect of the implementation of classroom management with the Visual, Auditory and Kinesthetic learning model (VAK) on the results of students' mathematics learning on the material system of linear equations of two variables (SPLDV) in SMPN 2 Rantau Selatan. This study used a quasi-experimental type of research with a pretest-posttest control group design. Data were collected through closed questionnaires and test questions in the form of pre-test and post-test each of which totaled 5 questions for each test—data analysis technique using multiple linear regression analysis technique. The results of the study show that the application of classroom management and the VAK learning model individually and together has a positive and significant effect on students' mathematics learning outcomes. The contribution of classroom management and the VAK learning model explains about 73.6% of the variation in student mathematics learning outcomes, according to the coefficient of determination (Adj R2 ) of 0.736. While the rest is influenced by other variables that are not examined by the researcher. This study concludes that classroom management using visual, auditory, and kinesthetic learning models affects students' mathematics learning outcomes, especially in the context of SPLDV. The implications of these findings guide educational practitioners in improving the effectiveness of mathematics learning in schools.